The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1080/15320383.2011.528466
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Atrazine Removal by Free and ImmobilizedArthrobacterSp. HB-5 in Soil and Wastewater

Abstract: In an attempt to remove atrazine in situ, high-efficiency atrazine-degrading Arthrobacter sp. strain and HB-5 immobilized on sodium alginate were introduced into two atrazine-polluted soils that are representative of soils in North China. Soil and wastewater with and without (controls) HB-5 or immobilized HB-5 were incubated at 25 • C after the addition of atrazine. Soil samples were collected after 0 d, 1 d, 3 d, 5 d, 7 d, 10 d, and 13 d, and wastewater samples were collected after 0 d, 1 d, 3 d, 7 d, 14 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Successful applications of atrazine bioremediation at high concentrations (samples from farm run-off waters or buffer solutions fortied with atrazine), from 10 to 30 ppm, have been reported [19][20][21][22] but most laboratory studies have used much higher atrazine concentrations that do not mimic actual environmental situations. Galindez-Najera et al reported complete removal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Successful applications of atrazine bioremediation at high concentrations (samples from farm run-off waters or buffer solutions fortied with atrazine), from 10 to 30 ppm, have been reported [19][20][21][22] but most laboratory studies have used much higher atrazine concentrations that do not mimic actual environmental situations. Galindez-Najera et al reported complete removal (i.e.…”
Section: Introductionmentioning
confidence: 99%